2016
DOI: 10.21037/jtd.2016.05.56
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related inflammation as predicting tool for treatment outcome in locally advanced and metastatic non-small cell lung cancer

Abstract: Background: Lung cancer is the leading cause of cancer deaths and the non-small cell lung cancer (NSCLC) represents 80% of all cases. In most cases when diagnosed, it is in locally advanced or metastatic stage, when platinum based doublet chemotherapy is the established therapeutic option for majority of the patients.Predictive factors to filter the patients who will benefit the most from the chemotherapy are not clearly defined. Objective of this study was to explore predictive value of pre-treatment C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In addition, NSCLC patients with preoperative thrombocytosis, platelet-to-lymphocyte ratio (PLR), neutrophil/lymphocyte ratio and prognostic nutritional index showed a significantly shorter disease-free survival (DFS) and OS (5)(6)(7). Similarly, elevated platelets count, C-reactive protein and high fibrinogen level were demonstrated as independent poor prognostic factors also in patients with advanced NSCLC (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NSCLC patients with preoperative thrombocytosis, platelet-to-lymphocyte ratio (PLR), neutrophil/lymphocyte ratio and prognostic nutritional index showed a significantly shorter disease-free survival (DFS) and OS (5)(6)(7). Similarly, elevated platelets count, C-reactive protein and high fibrinogen level were demonstrated as independent poor prognostic factors also in patients with advanced NSCLC (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Fbg may promote stable adhesion among tumor cells, platelets, and endothelial cells, [3,7,20,21] thereby further protecting the tumor cells from the impact of the immune system, enhancing the ability of cell establishment, deep infiltration, and metastasis. [4,22] Therefore, in our research and early studies, we found the later the N, M, and CS were, the higher the average levels of plasma Fbg were. [19]…”
Section: Discussionmentioning
confidence: 55%
“…Hyperfibrinogenemia can exist in many patients with malignant tumors including NSCLC and SCLC, which suggests a poor prognosis. [4,5,7,10,19] Fbg, synthesized by liver, is the highest content of coagulation proteins in plasma and can be converted to fiber polymer (insoluble fibrin) by activated thrombin. It plays a vital role in blood coagulation, fibrinolysis, inflammatory response, wound healing, and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations